PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN HANDPHONE SAMSUNG - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Demands for the needs of information very quickly and easily make the producers engaged in communications to interested new innovation by creating practical communication tools, one of which is to create a mobile phone (cell phone) or better known as mobile phones.